External validation of the SAPS3-CNIV score to predict hospital mortality following noninvasive ventilation: a retrospective single-centre study. Issue 2 (8th April 2019) - Huseini, Taha; Manners, David; Jones, Simon; Piccolo, Francesco
Prognostication tools are developed to assist clinical decision making and provide valid diagnostic and prognostic outcomes including mortality. Given significant disease and demographic heterogeneity, these tools have to be generally applicable to different patient populations. Therefore, once a model is developed it is internally and externally validated with subsequent clinical impact analyses after which its performance is evaluated and that particular model is then established. A retrospective single-centre study suggesting that patients with higher SAPS3-CNIV scores may be monitored in an ICU setting in order to reduce adverse patient events and optimal utilisation of resources http://ow.ly/F5qp30o2OT7